The Legal Protection of Men as Victims of Domestic Violence in Nigeria - Fasuyi, Precious O.; Olajide, Mary (ABUAD Law Journal, 2023)
Domestic violence has been identified as a human rights issue, and as such, it may result in violations of the victim's right to life, personal freedom, security, and freedom from torture or inhumane, cruel treatment. Over the years, societies and legal systems have placed focus on the eradication of domestic violence against women, while this serves a humanitarian purpose; violence against men has been neglected. Recent studies assert that domestic violence is a human problem rather than a gender problem. The aim of this paper is to examine the concept of domestic violence as a gender inclusive term, discuss the types and causes of domestic violence and the legal protection of men as victims of domestic violence. The research methodology adopted in this work is the doctrinal and qualitative methodology. It was found in the course of this research that there is an ever-increasing case of violence against men, with most of the cases underreported. In view of these, this paper concludes that the laws and government response are mostly inadequate. It is recommended that there is a need to recognise the fact that men are also victims of domestic violence, as this will be the very first step in unravelling the problem of domestic violence. In addition, there is also a need for the establishment of governmental agencies, training for enforcement officers who may be involved in the reporting process and public enlightenment for men to speak up.